2013
DOI: 10.1016/j.ygeno.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and psychosocial responses to genomic testing for colorectal cancer risk

Abstract: We conducted a translational genomics pilot study to evaluate the impact of genomic information related to colorectal cancer (CRC) risk on psychosocial, behavioral and communication outcomes. In 47 primary care participants, 96% opted for testing of three single nucleotide polymorphisms (SNPs) related to CRC risk. Participants averaged 2.5 of 6 possible SNP risk alleles (10% lifetime risk). At 3-months, participants did not report significant increases in cancer worry/distress; over half reported physical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 38 publications
4
48
0
Order By: Relevance
“…Next steps could also include the development and testing of print or interactive decision tools to facilitate telephone counseling at pre- and post-test disclosure using the extant literature as a guide. 28,30 Our finding that pre-disclosure confidence in coping with genetic test results was related to result disclosure to family members points to specific intervention targets. Findings from this study suggest that telephone counseling to return MMR test results is feasible within a research context, that many participants choose to disclose MMR results to family members and that those at greatest risk report sharing results with a healthcare professional.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Next steps could also include the development and testing of print or interactive decision tools to facilitate telephone counseling at pre- and post-test disclosure using the extant literature as a guide. 28,30 Our finding that pre-disclosure confidence in coping with genetic test results was related to result disclosure to family members points to specific intervention targets. Findings from this study suggest that telephone counseling to return MMR test results is feasible within a research context, that many participants choose to disclose MMR results to family members and that those at greatest risk report sharing results with a healthcare professional.…”
Section: Discussionmentioning
confidence: 86%
“…28 Tailored telephone approaches have been successful in increasing other health behaviors, including screening mammography and colorectal cancer screening; more recently, to return genetic test findings in clinical settings. 29,30 The often slow translation of research findings into clinical practice underscores the need to make relevant and clinically actionable research results available to interested research participants—and if appropriate, their families and healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…8,13,17,20 Previous research suggests theoretical models such as the HBM, 24 as used in this study, can explain the relationship between participants' perceptions and testing intentions. 14,16,21,28 Specifically, those who view genetic testing positively, and perceive that potential benefits can be accrued, are more likely to undergo testing.…”
Section: Willingness-to-paymentioning
confidence: 99%
“…11 The potential psychological impacts, along with concerns regarding family planning, fertility, lifestyle choices and health management, 5,12 indicate individualized management and genetic counseling should remain a priority. 3,10 A large body of research has investigated public [13][14][15][16][17] and patient 1,3,[18][19][20][21][22] perceptions of genetic testing, and reported that despite low levels of understanding, perceived benefits outweigh the risks. Patients' most highly-rated benefits include increased knowledge, better outcomes, and more effective prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies, mostly in the field of colorectal cancer, [33][34][35] focused on reducing multiple cancer risk factors, including smoking. The latest technical developments in the field of genomic testing suggest that genomic test procedures will have to include the provision of multiple-risk information 36 and that the issue of consultees' subsequent behavior is certainly a highly challenging one. 37 Three of the main limitations of this study need to be discussed.…”
Section: Original Research Articlementioning
confidence: 99%